ENFERMIDADES VIRAIS EM LAGOSTAS DO GÊNERO Panulirus: UMA REVISÃO SISTEMÁTICA: Viral diseases in lobsters of the genus Panulirus: a systematic review - da Silveira Siqueira, Ingrid Luana; Andrade, Thays; dos Santos Rocha, Rafael; de Carvalho Gaeta, Juliana; Maggioni, Rodrigo (Arquivos de Ciências do Mar, 2023)
Lobsters of the Panulirus genus are an important resource for world fisheries. However, like all marine crustaceans, they are affected by a variety of diseases caused by viruses, bacteria and parasites. The impact of diseases on the availability of this fishery resource is still poorly studied, and it is possible that it is magnified by the ongoing global climate changes. This systematic review addressed the viral pathologies that infect lobsters of the genus Panulirus, aiming to compile information about the clinical signs of these diseases, their characteristics in the tissues of infected animals and the methodologies used for their study. So far, only one lobster virus, specific to Panulirus genus, has been identified and described, the Panulirus argus virus (PaV1). In addition to that, the White spot virus (WSSV), which causes a serious disease in marine shrimp, has already been recorded in spiny lobsters. Keywords: Palinuridae, WSSV, PaV1, crustaceans.